Preparation of Photoluminescent Porous Silicon Nanoparticles by High‐Pressure Microfluidization. (24th January 2017) - Roberts, David S.; Estrada, Daniel; Yagi, Nobuhiro; Anglin, Emily J.; Chan, Nicole A.; Sailor, Michael J.
Abstract : The use of high‐shear microfluidization as a rapid, reproducible, and high‐yield method to prepare nanoparticles of porous silicon (pSi) with a narrow size distribution is described. Porous films prepared by electrochemical etch of a single‐crystal silicon wafer are removed from the substrate, fragmented, dispersed in an aqueous solution, and then processed with a microfluidizer, which generates high yields (57%) of pSi nanoparticles of narrow size distribution (PDI = 0.263) without a filtration step. Preparation of pSi nanoparticles via microfluidization improves yields (by 2.4‐fold) and particle size uniformity (by 1.8‐fold), and it lowers the total processing time (by 36‐fold) over standard ultrasonication or ball milling methods. The average diameter of the nanoparticles can be adjusted over the range 150–350 nm by appropriate adjustment of processing steps. If the fluid carrier in the microfluidizer contains an oxidant for Si, the resulting pSi particles are prepared with a core–shell structure, in which an elemental Si core is encased in a silicon oxide shell. When an aqueous sodium tetraborate processing solution is used, microfluidization generates photoluminescent core–shell pSi particles with a quantum yield of 19% in a single step in less than 20 min. Abstract : Microfluidization of porous Si films generates porous Si nanoparticles more rapidly, with a narrower size distribution, and in higher yield than can be achieved by other means. When the process is run in aqueous buffer, porous Si–SiO2 core–shell nanoparticles with high photoluminescence quantum yield are generated in a single step.